Obtenção de polissacarídeos sulfatados da alga marrom Dictyopteris justii e sua atuação contra injúrias em células renais provocadas por estresse oxidativo causado por peróxido de hidrogênio e oxalato - Melo, Karoline Rachel Teodosio de (2018)
Oxalate crystals are the major components of urinary calculi and these are closely related to oxidative stress in the pathophysiological condition of urolithiasis. It is estimated that around 10% of the world population is affected by this condition. Because of this, recent studies have looked for components that are capable of inhibiting this phenomenon. Studies with four fractions rich in sulphated polysaccharides from the brown algae Dictyopteris justii have shown that they are potent antioxidants, in addition to inhibiting the formation of these crystals in vitro. Based on the data obtained in the present study, these four fractions were rich in sulphated polysaccharides (DJ-0.3v, DJ-0.4v, DJ-0.5v, and DJ-1.2v) and their chemical composition and their action as protective and repair agents against the oxidative stress caused by hydrogen peroxide and oxalate. As results, it was observed that D. justii synthesizes populations of different sulfated polysaccharides. The first one, found in DJ-0.3v is rich in glucose, xylose and glucuronic acid and shows traces of fucose; the second (DJ-0.4v), has as a differential large amounts of fucose; thetwo populations found in DJ-0.5v and DJ-1.2v show only glucose and fucose traces, but differ in the amount of sulfate grouping. All sulfated polysaccharides showed total antioxidant capacity and modified the morphology of calcium oxalate crystals formed in vitro. The cytotoxicity study in HEK-293 (human renal embryonic cells) and MDCK (dog kidney cells) showed that the DJ- 0.3ve DJ-0.4v were only cytotoxic at concentrations above 2 mg / mL and DJ-0.5ve DJ-1.2v fractions were not cytotoxic until the maximal concentration studied (2mg / mL). The protective and repairing effect of these polysaccharides was also observed. Prophylactic treatment with all sulphated polysaccharides in HEK-293 cells up to a maximum concentration of 1 mg / mL maintained cell viability against the damage caused by hydrogen peroxide in these cells. On the other hand, with the exception of the DJ-0.3v fraction all fractions had a repairing effect on the cells, with emphasis on the DJ-0.5v fraction, whose treatment maintained the highest number of viable cells in both processes. In MDCK cells, the prophylactic effect was also verified and it was found that only treatments with DJ-0.4v and DJ-0.5v were able to protect cells against damage. In addition, treatment with these fractions decreased the expression of osteocalcin, a marker of bone differentiation, which is related to the process of mineralization and hypercalciuria, mechanisms involved in renal calculus formation. Possibly, these polysaccharides act by increasing the expression of antioxidant enzymes or acting together with them. The data obtained lead to the proposition that these polysaccharides are promising agents to be used in the treatment of urolithiasis.